The national physical development plan, Trinidad and Tobago. Volume II, Strategies and proposals - Government of the Republic of Trinidad and Tobago. Ministry of Finance, Planning and Development. (Town and Country Planning Division., 2011)
Presents alternative development strategies, spatial trends, planning proposals in the areas of land use, population and settlement, employment, agriculture, forestry, fishing, infrastructure, housing, tourism, environment and conservation.
Keywords: Physical planning - Trinidad and Tobago, Development planning - Trinidad and Tobago, Urban development, Land use – Policies, Rural planning, Demographics - Trinidad and Tobago, Employment, Environmental protection, Tourism, Housing, Infrastructure.